Characteristics of Spodosols, Limitation and Usage Potential - SUHARTA, NATA; YATNO, EDI (Jurnal Sumberdaya Lahan, 2009)
Spodosols characterized by the presence of spodic and albic horizons, are problem soils due to low productivity, coarse texture and low nutrient status. This soil was generally covered by alang-alang or shrub and bush. The soils were generally distributed in cold climate or wet tropical areas with high rainfall. The objectives of this paper were to discuss the characteristics ofSpodosols in Kalimantan and Sumatra and the possibility of their utilization. In Indonesia, this soil is found in Kalimantan, Sulawesi, Sumatra, and Papua Islands. Parent materials of the soils were originated from quartz sand, sediment or acid sedimentary rocks (quartz sandstone) with low nutrients status. Physiographically, the soils were distributed in alluvial plain, colluvial, sand beach, sand dune, tectonic plain and sandstone plateau on elevation of 5 to >1,500 m asl, with flat to nearly undulating relieves. The soil physical properties were characterized by coarse texture and the presence of root limiting layer such as fragipan, duripan, or placic horizon (organo-metal complex) with various depth. The soil chemical properties were characterized by acid soil reaction, very low exchangeable bases, P and K nutrient, and mineral reserve. Cation exchange capacity of the soils depends on their soil organic matter content. Based on the soil characteristics, most Spodosols were not suitable for agricultural land development. Therefore the Spodosols usages should be directed not only for production increases but also for environmental healthiness and soilcare. The Spodosols land that have been opened needs to be optimally used in order to increase soil quality through appropriate soil and plant management. The new land cleared for agriculture and production forest needs carefully actions with localizing the Spodosols distribution in order to maintain the natural vegetations as conservation forest or recreation areas.